Enterochromaffin 5-HT cells - A major target for GLP-1 and gut microbial metabolites - Mari L. Lund; Kristoffer L. Egerod; Maja S. Engelstoft; Oksana Dmytriyeva; Elvar Theodorsson; Bhavik A. Patel; Thue W. Schwartz (Elsevier, 2018)
Objectives: 5-HT storing enterochromaffin (EC) cells are believed to respond to nutrient and gut microbial components, and 5-HT receptor-expressing afferent vagal neurons have been described to be the major sensors of nutrients in the GI-tract. However, the molecular mechanism through which EC cells sense nutrients and gut microbiota is still unclear. Methods and results: TPH1, the 5-HT generating enzyme, and chromogranin A, an acidic protein responsible for secretory granule storage of 5-HT, were highly enriched in FACS-purified EC cells from both small intestine and colon using a 5-HT antibody-based method. Surprisingly, EC cells from the small intestine did not express GPCR sensors for lipid and protein metabolites, such as FFAR1, GPR119, GPBAR1 (TGR5), CaSR, and GPR142, in contrast to the neighboring GLP-1 storing enteroendocrine cell. However, the GLP-1 receptor was particularly highly expressed and enriched in EC cells as judged both by qPCR and by immunohistochemistry using a receptor antibody. GLP-1 receptor agonists robustly stimulated 5-HT secretion from intestinal preparations using both HPLC and a specific amperometric method. Colonic EC cells expressed many different types of known and potential GPCR sensors of microbial metabolites including three receptors for SCFAs, i.e. FFAR2, OLF78, and OLF558 and receptors for aromatic acids, GPR35; secondary bile acids GPBAR1; and acyl-amides and lactate, GPR132. Conclusion: Nutrient metabolites apparently do not stimulate EC cells of the small intestine directly but through a paracrine mechanism involving GLP-1 secreted from neighboring enteroendocrine cells. In contrast, colonic EC cells are able to sense a multitude of different metabolites generated by the gut microbiota as well as gut hormones, including GLP-1. Keywords: Metabolite GPCR, Nutrient sensing, Gut microbiota, Gut hormone, Enteroendocrine, Afferent vagal nerves